2010
DOI: 10.1111/j.1748-1716.2010.02200.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory function of amphibian skin: integrating epithelial transport, capillary blood flow and behaviour

Abstract: Terrestrial anuran amphibians absorb water across specialized regions of skin on the posterioventral region of their bodies. Rapid water absorption is mediated by the insertion of aquaporins into the apical membrane of the outermost cell layer. Water moves out of the epithelium via aquaglyceroporins in the basolateral membrane and into the circulation in conjunction with increased capillary blood flow to the skin and aquaporins in the capillary endothelial cells. These physiological responses are activated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…A physiological study using the pelvic skin of B. bufo showed that perfusion of the skin with a Ringer solution sustained the elevated high water flux by AVT, but stopping the perfusion resulted in a dramatic drop in the water flux (43). It was also reported that dehydrated bufonids responded to water contact with a rapid increase in blood flow, as well as water uptake, in the pelvic skin (38,39,44). Furthermore, IP injection to B. bufo facilitates not only cutaneous water uptake but also capillary perfusion, suggesting an important role of sympathetic nervous system in the regulation of cutaneous blood flow and water absorption in vivo (38).…”
Section: Discussionmentioning
confidence: 96%
“…A physiological study using the pelvic skin of B. bufo showed that perfusion of the skin with a Ringer solution sustained the elevated high water flux by AVT, but stopping the perfusion resulted in a dramatic drop in the water flux (43). It was also reported that dehydrated bufonids responded to water contact with a rapid increase in blood flow, as well as water uptake, in the pelvic skin (38,39,44). Furthermore, IP injection to B. bufo facilitates not only cutaneous water uptake but also capillary perfusion, suggesting an important role of sympathetic nervous system in the regulation of cutaneous blood flow and water absorption in vivo (38).…”
Section: Discussionmentioning
confidence: 96%
“…More research is needed to understand the mechanisms underlying the behavioural response demonstrated by the toads. Amphibians may be able to detect these chemical metabolites through the chemo-or pain receptors in their skin (Hillyard & Willumsen, 2011), which could facilitate the detection and avoidance of external stimuli through epidermal contact (for example see Kiesecker et al, 1999). Pavlovian conditioning predicts that chemicals that induce negative stimuli, for example pain or itching, or are associated with allelochemicals, for example odours, would produce a strong behavioural avoidance response.…”
Section: Discussionmentioning
confidence: 99%
“…Bd metabolites triggered the associational behavioral avoidance in southern toads, which is not surprising given that many vertebrate species are capable learning to avoid a cue that is accompanied by a painful stimulus (Dunlop et al 2006 , and thus exposure to metabolites might indeed be painful. Amphibians may be able to detect these chemical metabolites through the chemo-or pain receptors in their skin (Hillyard & Willumsen 2011), which could facilitate the detection and avoidance of external stimuli through epidermal contact (for example see Kiesecker et al 1999). Pavlovian conditioning predicts that pain inducing chemicals would produce a strong behavioral avoidance response.…”
Section: Discussionmentioning
confidence: 99%